IMPROVING READING COMPREHENSION OF THE EIGHT GRADE STUDENTS OF SMP NEGERI 13 PALU THROUGH CHORAL READING STRATEGY - Karunia Rahman (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Study This aiming For evaluate performance business service TS Futsal sports in Gorontalo with use Balanced Scorecard approach , which includes four perspective main : finance , customers , internal business processes , and learning and growth . Data obtained through questionnaire distributed​ to customers and employees between February until September 2024. Research results show that performance TS Futsal 's finances are in good condition with an average Net Profit Margin (NPM) of around 83.75%. In perspective customer , level satisfaction show results positive , especially in service and convenience booking . Perspective internal business indicates that innovation technology has increase efficiency operational , although Still There is need For repair in matter Work The same team. In perspective learning and growth , employees feel involved in taking decision , but communication between management and employees Still need repaired.In Overall , the implementation of the Balanced Scorecard provides description comprehensive about TS Futsal performance and can become strong foundation​ For planning strategic in the future . Research This expected become reference for business other services in increase performance and power compete .